PENGEMBANGAN VIDEO TUTORIAL POLA DASAR DAN PECAH POLA WANITA BERBASIS COMPUTER-AIDED DESIGN (CAD) MENGGUNAKAN APLIKASI POWERDIRECTOR 18 PADA PROGRAM STUDI PENDIDIKAN TATA BUSANA - Luthfi, Fatiyah; Salsabilah; Almindri, Windea; Hanifa, Syifa; Simanjuntak, Steven Ricky Yohanes; Silalahi, Jesy Tamaro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of technology in education requires the development of innovative learning media to enhance the effectiveness of the learning process, particularly in vocational fields such as fashion education. The teaching of basic patterns and pattern manipulation, which was previously conducted manually, is now transitioning to digital systems based on Computer-Aided Design (CAD). However, its implementation still faces several challenges, including limited access to learning media that support students’ independent learning. This condition highlights the need for interactive, flexible, and accessible instructional media. This study employs a Research and Development (R&D) approach to develop a CAD-based video tutorial using PowerDirector 18 as an innovative learning medium. The validation results indicate that the product has a very high level of feasibility, with a final score of 85.33% from media experts and an average score of 4.38 from material experts. In addition, initial student responses show a high level of practicality, with scores ranging from 4 to 5. Although minor revisions were required in the audio aspect, the product is generally considered valid and suitable for use. To further examine its effectiveness, a comparison of pre-test and post-test results will be conducted using N-Gain analysis. The findings of this study are expected to contribute to improving learning quality and serve as a reference for the development of technology-based learning media in fashion education.